Strain effect on structural, electronic and optical properties of Gra/MoS2 heterobilayer - Hassan, Hassan Ahmed Jaber; Chan, Kar Tim; Mohd Shah, Nurisya; Mohd Noor, Nurfarhana; Ooi, Raymond Chong Heng (Institute of Physics, 2024)
Heterobilayers formed by stacking graphene and MoS2 monolayers have been successfully synthesized in the laboratory, presenting a highly promising material with versatile applications due to its flexibility and enhanced optical properties. In this study, we employ density functional theory to investigate the impact of biaxial and uniaxial strain on the structural, electronic and optical properties of Graphene/MoS2 (Gra/MoS2) heterobilayer. The unstrained Gra/MoS2 is shown to be a thermodynamically stable structure with binding energy − 0.736 eV and a band gap of 1.899 meV, which opens at the Dirac point of graphene. Gra/MoS2 is also shown to have a better refractive index and absorption coefficient when compared to MoS2 monolayer in the visible region. Under biaxial strain, heterobilayer became unstable as the structure of both monolayers changed. The variation of biaxial strain from −4% to 4% enables tuning of the band gap within a range of 1.07-6.623 meV. The Fermi level shifted towards the conduction band under compressive strain and towards the valence band under expansive strain. Manipulation of biaxial strain also facilitates tunability in energy peaks for optical properties such as the real and imaginary parts of the dielectric function, refractive index and absorption coefficient in the visible spectrum. In contrast, uniaxial strain induces minimal changes in the overall structure and stability of the heterobilayer, resulting in a limited band gap range of 1.118-2.4 meV. Furthermore, uniaxial strain fails to introduce significant tunability in the optical properties of the heterobilayer.